FMS-like tyrosine kinase (FLT3) gene ITD mutation in acute myeloid leukemia - Kušec, Rajko (Zdravniški vestnik, 2004)
Background. FLT3 is a class III receptor tyrosine kinase expressed in normal stem cells and blasts of myeloid leukemia. Internal tandem duplication (ITD) of the FLT3 gene affecting the exons 14 and 15 leads to ligand-independent FLT3 dimerization and constitutive activation. This stimulates proliferation and induces inhibition of apoptosis which contributes to leukemogenesis. We have screened a panel of acute myeloid leukemia (AML) patients for the occurrence of FLT3/ITD mutation and correlated this mutation to patients' survival and basic hematological parameters. Methods. RT-PCR for ITD in exons 14 and 15 of FLT3 gene was done on bone marrow samples of 67 AML patients at diagnosis. Results. There was a 16.4% incidence of FLT3/ITD mutation in the cohort of examined patients. By cytognetic subgroups there were 2/6 t(15; 17) and 1 of 4 t(8;21) positive patients. The rest had normal and 2 had complex karyotype. Majority were of FAB M2 or M4 phenotype. For a subset of patients taken into comparative survival analysis there was a clear disadvantage for FLT3/ITD patients. No difference was found for basic hematological parameters between two groups. Conclusions. As it is evident today that FLT3/ITD is the single most common genetic abnormality in AML that also presents unfavorable clinical prognostic marker, it should be included in molecular diagnostic testing of acute myeloid leukemia.
Keywords: Eksoni; Exons; Fenotip; Genes, Fms; Genetics; Geni fms; Kariotip, določanje; Karyotyping; Leukemia, Myelocytic, Acute; Levkemija mielocitna, akutna; Phenotype; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Preživetje, analiza; Prognosis; Prognoza; Survival Analysis